دور المذاهب الفقهية في الانحرافات السلوكية والفكرية ونظرة الشريعة الإسلامية - Niteh, Muhammad Yosef; Samian, Abdullatif; Basir, Aminuddin; Muhammad Husni, Ahmad; Ahmad, Maad (Pusat Pengurusan Penyelidikan (RMC), Kolej Universiti Islam Antarabangsa Selangor (KUIS), 2016)
The idea of this research is to give profile appearances and practices which do not comply with Islamic law and this is not limited to the large number of these appearances, but to stand on these appearances and knowing the view of Islamic law towards it, away from the statistics and numbers, these ideologies have its aspects and connotations from which to judge that this behaviour and this thought is not one of the characteristics of Islamic law, but it is an outsider entered the Islamic nation and affect the Muslims which led to an imbalance in the morals and influence the right and proper understanding of Islamic law. This research is to prove the deviations in behavior are due to the affected by the intellectual currents or ideological invasion. The researcher followed two approaches, namely inductive which is to extrapolate the views of ulamak, scholars and literature related to the subject with reference to forensic evidence from the Quran and the Sunnah. The analytical approach in terms of reference to the linguistic meanings, idiomatic and analyse the views of intellectuals, and scholars. The most important results is there are real attempts by the doctrines of thought toward the change in the faith and the pattern of Muslim life; to keep them away from Islamic law; and the occurrence of schizophrenia in the faith.